Pilots using selective serotonin reuptake inhibitors compared to other fatally injured pilots. (October 2017) - Rogers, Paul; Hileman, Christy; Salazar, Guillermo; Cliburn, Kacey; Paskoff, Lawrence; Hathaway, William; Gildea, Kevin; Tejera Villalaz, Victor Hugo
Highlights: The Federal Aviation Administration allows pilots to use selected Selective Serotonin Reuptake Inhibitors (SSRI) as of April 5, 2010. A Poisson regression model was employed to quantify risk in terms of incident rate ratios. There was no direct evidence that SSRIs were a danger to flight safety. Abstract: Selective Serotonin Reuptake Inhibitors (SSRI) were a disqualifying medication for U.S. civil pilots before April 5, 2010. After this date, a Federal Aviation Administration policy was created that allowed airmen, on select SSRIs, a pathway to hold a valid medical certificate. The purpose of this study was to provide a detailed look at SSRIs in the U.S. pilot population since the inception of this new policy. We examined the toxicology results from fatally injured airmen in addition to outcomes concerning pilots who are participating in the program. This study examined data from the Civil Aerospace Medical Institute's Bioaeronautical Sciences Research Laboratory in conjunction with the Medical Analysis Tracking Registry and the Document Imaging and Workflow System. A count-based regression model quantified the relationships between positive SSRI findings with additional factors of interest. These factors included pilot rating, ethanol, and first generation antihistamines. There were 1484 fatally injured airmen over the six year study period, of which 44-tested positive for an SSRI. First-generation antihistamines were statistically associated with positive findings of SSRIs.